The impact of restaurant tax receipts on local revenue in the Cibinong area: - - Amin Setio Lestiningsih -; Sabil Sabil; Dwiyatmoko Puji Widodo; Dinda Faudiasari (Universitas Negeri Padang, 2021)
The State of Indonesia as a unitary state adheres to the foundation of decentralization. Several sources of state revenue in the APBN come from taxes, one of which is the restaurant tax. The restaurant tax is a regional tax that will increase the local revenue that will be used to finance infrastructure development in the area. The purpose of this research is to identify the effect of the restaurant tax on the original income of the Cibinong area. This research only cites the scope of restaurant tax revenues and the original income of the Cibinong area with 24 processed information, from January 2019 to December 2020. The information analysis method uses assurance coefficient experiments and simple regression meetings. Based on the results of the measurement experiments, it is obtained The R-squared obtained is 0, 925 or 92, 5%. These results prove that the restaurant tax-free elasticity has an impact of 92.5% in regional taxation, and the 7.5% more is influenced by other aspects that have not been carefully researched. Based on the results of the regression meeting, the equation is Y= 0.060 + 1.008X, if Restaurant Tax Revenue faces an escalation of Rp. 1 until the Cibinong Regional Tax Income will increase by 1.008. If there is no restaurant tax income, up to the original Cibinong area income. of 0.060